Prevalence and Severity of Menopausal Symptoms Among Women – A Community-Based Cross-Sectional Study - Timi Thomas; Neetha Kamath; Ajay Kumar; Fatima D’Silva; Prasanna Kumar Shetty (Online Journal of Health & Allied Sciences, 2021)
The women aging process is characterized by a gradual transition from reproductive to non reproductive life period. These changes in aging during menopause are accompanied by a wide range of physiological as well as psychological disturbing symptoms. Menopausal symptoms have been widely studied in women from western societies, but less information is available for women of non-western ethnic groups. There is evidence of differences in the prevalence of symptoms in Asian versus Western women. This study evaluates the menopausal symptom of women aged between 48 to 55 years which is important to understand the prevalence and plan for the remedial measures and also to create health awareness among women. Objective: To assess the prevalence of menopausal symptoms among women. Methods: A community-based cross-sectional study was carried out, using a stratified sampling technique. The study was conducted in three Primary Health Centres of Mangalore Taluk: Kotekar, Natekal and Mudipu. A total of 1034 samples between the ages of 48–55 years were screened under 16 sub-centers. Results: The average age among menopausal women was 49.8 ± 1.51 years. The average age of attaining menopause among the participant was 48.26 years. The most common symptom reported under the domains of vasomotor is hot flushes. About 83% of the participants were experienced with hot flushes and 71% of participants are reported with night sweats. The most common psychosocial symptoms experienced by menopausal women were forgetfulness [72%], feeling anxious [52%]. The most reported physical symptoms among study participants were tiredness [80%], lack of energy [71.2%] and difficulty in sleeping [60%]. The least reported domains of menopausal symptoms were frequent urination and urinary tract infections. Under the sexual complaints, 82% of the participants reported changes in the sexual desire. Conclusion: The study has shown that the prevalence of classical menopause symptoms like profuse sweating along with hot flushes, increased anxiety, depression, wanting to be alone, and urinary tract infections were lower but, symptoms like hot flushes, night sweats, tiredness, difficulty in sleeping, changes in sexual desire were the prominent symptoms among the study participants.